Review on the impact of marine environment on the reliability of electronic packaging materials - Lang, Fengyong; Zhou, Zhenrui; Liu, Jia; Cui, Meng; Zhang, Zhongqing (Frontiers in Materials, 2025)
Marine environments pose significant challenges to the reliability of electronic packaging materials. This review summarizes the main degradation mechanisms and reliability impacts of electronic packaging materials under marine conditions, including salt spray corrosion, high humidity, thermal cycling, and mechanical shock. Salt spray corrosion initiates localized galvanic corrosion through chloride ion (Cl−) diffusion, creating corrosion pits and stress concentration, thereby accelerating electrochemical-mechanical coupled failures. High humidity promotes moisture ingress into polymer packaging materials, resulting in hygroscopic plasticization, weakened interfacial adhesion, and delamination failure. Thermal cycling, due to mismatched coefficients of thermal expansion (CTE), induces growth of interfacial intermetallic compound (IMC) layers at solder joints and creep-fatigue interactions, further promoting interfacial crack propagation. Mechanical shock generates transient, high-strain-rate loading, rapidly initiating and propagating cracks within brittle packaging structures, ultimately leading to structural failure. Additionally, this paper discusses the current status and limitations of Physics of Failure (PoF)-based reliability models such as the Coffin-Manson and Arrhenius models for evaluating electronic packaging reliability in marine environments. Finally, it suggests that future studies should further develop multiphysics coupling models to more accurately predict long-term material performance under extreme marine conditions.